PLACE OF UZBEK ANIMATED FILMS IN THE WORLD OF ANIMATED FILMS - Talabbaev Rustam Ergashalievich (Galaxy International Interdisciplinary Research Journal, 2022)
Animated films occupy one of the important places in the life of a modern person. Images of popular animated characters accompany a person from early childhood. The most significant memories, associations, sensations are associated with them. The artistic and aesthetic impact of the figurative system of animated films on the formation of the worldview of a growing personality is enormous. This is the most psychologically comfortable (easy, accessible, convincing) channel of communication, transmission of socio-cultural norms and values, contributing to the formation of attitudes, interests and needs of the majority of the population from an early age. Before a person enters the market with a public mass culture, he has already come into contact with humanistic values, cultural traditions, national customs in the world of animation. Subsequently, he recognizes the meanings and meanings assigned to them in his personal development, discovering the causal relationships that exist in his mind.